Mexico : Review Under the Flexible Credit Line-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Mexico's Review under the Flexible Credit Line. Mexico's very strong policies and policy frameworks have helped it navigate successfully a complex external environment characterized by the heightened risk of protectionism and financial market volatility. Inflation is above the central bank's target, reflecting mainly the transitory effects of the liberalization of domestic fuel prices and the pass-through from the currency depreciation. Although the global environment and financial stability have improved somewhat recently, downside risks affecting Mexico remain elevated amid continued uncertainty about the outcome of the discussions with the United States on trade, as well as a possible renewed surge in capital flow volatility.